USE OF BIG BOOK MEDIA TO IMPROVE LANGUAGE AND KNOWLEDGE OF FLOOD DISASTER IN EARLY CHILDREN AT NADA ASHOBAH KINDERGARTEN SURABAYA - Haniya; Rachma Hasibuan (International Journal of Teaching and Learning, 2024)
The Big Book is a learning medium in the form of a storybook with large-sized illustrations and text. The large size is specifically designed to attract students' attention and facilitate the learning process. This study presents information about flood disasters using the Big Book as the medium. The research aims to introduce education related to flood disasters and their mitigation. The research method used is descriptive qualitative. The subjects of the study are 20 children aged 5-6 years at TK IT Nada Ashobah Surabaya. Data collection techniques are based on observation, interviews, and documentation. Creswell's data analysis aims to obtain a narrative, phenomenological, grounded theory, ethnographic, and case study approach with a series of events related to human experiences. This research can be implemented in early childhood education, especially in learning related to flood disasters, to improve language skills and knowledge about flood disasters. The results of this study indicate that the Big Book medium is very effective in enhancing children's reading abilities and knowledge about flood disaster mitigation. With an attractive and interactive design, the Big Book helps children more easily recognize letters, words, and important steps in facing floods.